Prevalence and symptomatology of polycystic ovarian syndrome in Indian women: is there a rising incidence? - Choudhary, Anjali; Jain, Shweta; Chaudhari, Priyanka (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Polycystic ovarian syndrome [PCOS] is a complex ill understood hormonal disorder resulting in myriads of symptoms like irregular menses, hyperandrogenism, metabolic disturbances and infertility. It occurs in about 8-11% of reproductive age group women. Recently changing lifestyles and rising obesity worldwide have contributed to rise in the incidence of PCOS. Objective of the present is to study the prevalence and symptomatology of PCOS in Indian women. Methods: 170 women in reproductive age group, with irregular menstrual cycles attending OPD, voluntarily participated in a cross sectional study. All were subjected to detailed history, examination and investigated with a battery of lab tests to confirm PCOS. Out of 170 women investigated 70 women with features of PCOS were included in the study (diagnosed as PCOS by NIH criteria). Results: The overall prevalence of PCOS in the study population was, 41%. It was 16% in married women and 24 % in unmarried girls. Common menstrual irregularity was-oligomenorrhea (40%), Menorrhagia (12.8%) amenorrhea (11%). Common symptoms were hirsutism, acne, infertility and alopecia. Conclusions: PCOS is rising in young women and to some extent the changing lifestyle in urban women may be linked to it. There in a world-wide increase in the incidence of obesity, diabetes mellitus and metabolic syndrome, PCOS and its accompanying insulin resistance is contributing to it. Treating PCOS and its complications is adding to health care burden.